2003
DOI: 10.4049/jimmunol.170.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity Mediated by the Cytokine IL-1 Homologue 4 (IL-1H4/IL-1F7) Induces IL-12-Dependent Adaptive and Profound Antitumor Immunity

Abstract: Recently, several novel members of the IL-1 family have been identified. The possible therapeutic utility and the underlying biologic role of these new members remain unclear. In the present study we analyzed the anti-tumor activity of human IL-1 homologue 4(IL-1H4; renamed IL-F7) by adenovirus-mediated gene transfer (AdIL-1H4) directly into murine tumors. In vitro expression analysis showed that IL-1H4 was a secretory protein. Treatment of an established MCA205 mouse fibrosarcoma by single intratumoral inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 32 publications
3
78
4
Order By: Relevance
“…IL‐37 has been identified as a natural suppressor of innate inflammatory and immune responses 8, 12. Recent studies have indicated that IL‐37 plays a protective role in tumor progression in mouse fibrosarcoma,9 human lung cancer,14, 42 hepatocellular carcinoma,13 breast cancer,43 cervical cancer,44 and renal cell carcinoma 45. Zhang et al15 found that IL‐37 inhibits colon cancer progression via β‐catenin suppression and that a lack of IL‐37 is associated with poor survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL‐37 has been identified as a natural suppressor of innate inflammatory and immune responses 8, 12. Recent studies have indicated that IL‐37 plays a protective role in tumor progression in mouse fibrosarcoma,9 human lung cancer,14, 42 hepatocellular carcinoma,13 breast cancer,43 cervical cancer,44 and renal cell carcinoma 45. Zhang et al15 found that IL‐37 inhibits colon cancer progression via β‐catenin suppression and that a lack of IL‐37 is associated with poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, entirely distinct with most IL‐1 family members, that are characterized with proinflammatory functions, IL‐37 has emerged as an important inhibitor of the innate immune response. With the accumulated evidence, IL‐37 has been recognized as a typical anti‐inflammatory cytokine related to autoimmune diseases, endotoxemia, inflammatory liver injury, obesity, and cancer 8, 9, 10, 11, 12. Gao et al9 found that the intratumoral injection of IL‐37 inhibited tumor growth and the antitumor activity of IL‐37 was abrogated in mice models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C57BL/6 mice (H-2 b ), C57BL/6-background Thy1.1 (B6.PL-Thy1 a /CyJ), perforin-deficient (C57BL/6-Pfptm1 sdz ), IFN-␥-deficient (B6129S7-ifng), and FasL-deficient (B6Smn, C3H-Fasl gld ) mice (6 -8 wk old) were purchased from The Jackson Laboratory. IL-12/IL-23 p40-deficient animals were maintained as described previously (38). Animals were handled under aseptic conditions in microisolator cages within the Central Animal Facility at the University of Pittsburgh per an Institutional Animal Care and Use Committee-approved protocol and in accordance with recommendations for the proper care and use of laboratory animals.…”
mentioning
confidence: 99%
“…Zhao et al and Gao et alfound that intra-tumoral injection of IL-37 leads to strong inhibition of tumor growth and this effect is dependent on T cells and B cells as it is reversed in IL-12-, IFN-γ-or Fas ligand-deficient mice and in nude and SCID mice (64,88). Yin et al showed that a single nucleotide polymorphism in the IL-37 gene (rs3811047) is significantly associated with coronary artery disease (CAD), which suggests that IL37 represents a new susceptibility gene for CAD (89).…”
Section: Potential Roles Of Il-37 In Clinical Therapymentioning
confidence: 99%